Marine antifouling property of PMMA nanocomposite films: Results of laboratory and field assessment. (October 2016) - Sathya, S.; Murthy, P. Sriyutha; Das, Arindam; Gomathi Sankar, G.; Venkatnarayanan, S.; Pandian, R.; Sathyaseelan, V.S.; Pandiyan, V.; Doble, M.; Venugopalan, V.P.
Abstract: In the present work, hydrophobic (contact angle ∼108°) poly methyl methacrylate (PMMA) films were developed by a simple room temperature drop-cast method based on slow solvent evaporation process. Further, PMMA nanocomposites (NCs) were developed by impregnating PMMA with nanoparticles (0.1% w/v) of copper oxide (CuO), cetyltrimethyl ammonium bromide (CTAB) capped CuO (CuO-CTAB) and zinc oxide (ZnO). The PMMA and NCs were tested against attachment of marine bacteria, microalgae (diatoms) and barnacle larvae in laboratory as well as in the sea. At low loading of nanoparticles (0.1% w/v), the PMMA NCs inhibited bacterial settlement (24 h assay) by 97–99% in the laboratory and by 40–69% in the field exposure studies. They also inhibited diatom attachment (24–38%) in laboratory and in the sea (80–95%). NCs successfully inhibited (100%) barnacle settlement and metamorphosis and caused mortality to the extent of 22–44% in exposed cypris larvae. Incorporation of nanoparticles in PMMA confers antifouling property to the polymer at greatly reduced metal release rates as compared to conventional antifouling paints. Results of the study indicate that PMMA NCs are promising as low cost antifouling coatings for static moored/submerged structures in the ocean due to their efficacy at low environmental metal release. Highlights: Hydrophobic PMMA films could be prepared by a simple, slow solvent evaporation based, drop-casting method. PMMA nanocomposites at low nanoparticle loading (0.1% w/v) effectively reduce bacterial and barnacle attachment. Metal oxide nanocomposites show antifouling effect at low environmental release of metal.